PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN MULTIMEDIA TERHADAP MOTIVASI BELAJAR PADA SISWA KELAS V MADRASAH IBTIDAIYAH MUHAMMADIYAH MIRI KECAMATAN POLOKARTO KABUPATEN SUKOHARJO TAHUN PELAJARAN 2021/2022 - Indi Sularsih; Arif Effendi (Jurnal Inovasi Penelitian, 2022)
Indi Sularsih and Arif Effendi, thesis, The effect of using multimedia learning media on learning motivation in fifth grade students of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo, academic year 2021/2022, Surakarta Mamba’ul ‘Ulum of Islamic Instutute. This research wish to know the use of multimedia learning media in fifth grade students of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo for the academic year 2021/2022 ; wish to know the learning motivation of the fifth grade student of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo for the academic year 2021/2022 ; and wish to know the correlation between multimedia learning media and learning motivation of the fifth grade student of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo for the academic year 2021/2022 This research is a type of correlational quantitative research that correlates two variables, Subject in this study are the fifth grade students of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo academic year 2021/2022. with a population of 32 students with no sample. The data analysis technique to test the hypothesis in this study is to use the Product Moment correlation analysis technique. The results showed that the use of multimedia learning media in fifth grade students of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo for the academic year 2021/2022 was in the enough category ; the learning motivation of the fifth grade student of muhammadiyah ibtidaiyah madrasah at Miri district of Polokarto regency of Sukoharjo for the academic year 2021/2022 was the enough category; The results of correlation are r xy = 0,32 or the category is poor.